Canonical and noncanonical Wnt pathways: a comparison between endometrial cancer type I and atrophic endometrium in Brazil - Menezes, Marina de Pádua Nogueira; Oshima, Celina Tizuko Fujiyama; Badiglian Filho, Levon; Gomes, Thiago Simão; Barrezueta, Luis Fernando Mesias; Stávale, João Norberto; Gonçalves, Wagner José (São Paulo Medical Journal, 2011)
CONTEXT AND OBJECTIVE: The Wnt pathway is involved in tumorigenesis of several tissues. For this reason, we proposed to evaluate Wnt gene expression in endometrial cancer type I. DESIGN AND SETTING: Cross-sectional study on materials gathered from the tissue bank of the Department of Pathology, Universidade Federal de São Paulo. METHODS: Endometrial specimens were obtained from surgeries performed between 1995 and 2005 at São Paulo Hospital, Universidade Federal de São Paulo. The material was divided into two groups according to tissue type: Group A, atrophic endometrium (n = 15); and Group B, endometrial adenocarcinoma (n = 45). We compared the immunohistochemical expression of Wnt1, Frizzled-1 (FZD1), Wnt5a, Frizzled-5 (FZD5) and beta-catenin between endometrial cancer type I and atrophic endometrium. RESULTS: Regarding Wnt1, FZD1 and Wnt5a expression, no significant association was observed between the groups. A significant association was observed between the groups in relation to FZD5 expression (P = 0.001). The proportion of FZD5-positive samples was significantly higher in group A (80.0%) than in group B (31.1%). Regarding the survival curve for FZD5 in group B, we did not find any significant association between atrophic endometrium and endometrial adenocarcinoma. We also did not find any significant association regarding beta-catenin expression (P = 1.000). CONCLUSION: FZD5 is downregulated in endometrial adenocarcinoma, in comparison with atrophic endometrium.